Climate variability on the Adriatic seaboard during the last glacial inception and MIS 5c from Frasassi Cave stalagmite record. (1st December 2018) - Vanghi, V.; Borsato, A.; Frisia, S.; Drysdale, R.; Hellstrom, J.; Bajo, P.
Abstract: A stalagmite (FR16) from Frasassi Cave, located near the Adriatic coast of the Italian peninsula, offers a 16 kyr petrographic and stable isotope record spanning from 112.8 ± 1.5 ka to 96.6 ± 1.0 ka, corresponding to the interval from marine isotope stage (MIS) 5c to MIS 5d. The physical characteristics of FR16 calcite, allowed for a thorough understanding of the processes controlling isotopic changes, because fabrics as well are controlled by the environmental parameters within the cave that reflect external climate forcing. The FR16 δ 13 C profile matches fabric changes where columnar fabric usually corresponds to more negative values and micrite/microsparite layers to less negative δ 13 C values, and with the North Greenland Ice-core Project (NGRIP) δ 18 O record with more negative δ 13 C values during interstadials GI24 and GI23. This suggests a hydrological sensitivity for the two proxies, and their variability can be linked to recharge changes. On the other hand, the response to Greenland events appears subdued in the δ 18 O record and the trend mimics instead the Northern Hemisphere (NH) summer insolation with more negative δ 18 O values corresponding to the maximum insolation centred at ca. 105 ka. This behaviour can be explained by the higher sensitivity of δ 18 O to rainfall seasonality, moisture source and trajectories, whose combined effect attenuated the stadials/intersadials signal in the stalagmite. Highlights: 16 kyr stable isotope and petrographic stalagmite record from Frasassi cave (Italy), covering the last glacial inception. Petrographic observations benchmark the interpretation of the δ 13 C profile. Stalagmite δ 13 C shows a general increasing trend with short-lived more positive shifts coinciding with NGRIP stadials. The δ 18 O profile trend follows the NH summer insolation, with the most negative values recorded at higher insolation. The δ 18 O signal of the stalagmite seems to be primarily controlled by moisture provenance and rain shadow effects.